Cross cultural awareness and social justice in counseling/ edited by Cyrus Marcellus Ellis and Jon Carlson - "Ellis, Cyrus Marcellus (ed.)" (New York, 2008)
Many societal and cultural changes have taken place over the past several decades, almost all of which have had a significant effect on the mental health professions. Clinicians find themselves encountering clients from highly diverse backgrounds more and more often, increasing the need for a knowledge of cross-cultural competencies. Ellis and Carlson have brought together some of the leaders in the field of multicultural counseling to create a text for mental health professionals that not only addresses diversity but also emphasizes the counselor$1 (Bs role as an advocate of social justice. The theoretical foundation for this book rests on research into diversity, spirituality, religion, and color-specific issues. Each chapter addresses the unique needs and relevant issues in working with a specific population, such as women, men, African Americans, Asian Americans, Spanish-speaking clients, North America$1 (Bs indigenous people, members of the LGBT community, new citizens, and the poor, underserved, and underrepresented. Issues that enter into the counselor-patient relationship are discussed in detail for all of these groups, with the hope that this will lead to a greater understanding and sensitivity on the part of the counselor for their patients. This is an important and timely book for both counselors-in-training and those already established as professionals in today$1 (Bs highly diverse and constantly-changing society.s
Keywords: Cross-cultural comparison-United States